Hydraulic Characteristics of Flow over Circular Crested Weirs - Jaafer, Rondik A.; Hussen, Bshkoj S. (Science Journal of University of Zakho, 2016)
In this investigation nine models of circular crested weir were constructed and tested during an experimental study. Crest radius( r)  of the weir was varied three times; 2.5 cm, 3.1cm and 3.75cm. For every crest radius the weir height (p) was varied three times; 15cm, 20cm and 25cm. The result was showed that the discharge coefficient (Cd) affected by two factors; head above the weir to the crest height (h/p) and head above the weir to the crest radius (h/r). It was observed that coefficient of discharge (Cd) increased with increasing (h/p) for the similar height of weir and for definite value for the ratio h/p the (Cd) value increased with increasing the crest height (p). Also it was found that coefficient of discharge (Cd) increased with increasing (h/r) for the similar crest radius and for definite value for the ratio (h/r), the (Cd) value increased with increasing the crest radius (r). A simple power experiential expression was found for the variation of (Cd) with (h/p) and (h/r) with high correlation coefficient.
Keywords: Circular weir; Discharge coefficient; crest shape